Deskripsi Tentang Pemanfaatan Sumber Mata Air Jompi Kelurahan Laende Kecamatan Katobu Kabupaten Muna - Vebrianti, Vebrianti; Amaluddin, La Ode; Musyawarah, Rahma (UNIVERSITAS NEGERI MAKASSAR, 2019)
Raha City is located on the coast of the Buton Strait, the capital of Muna Regency, Southeast Sulawesi Province. The total area of this city is 47.11 km2 consisting of 12 villages and 7 villages. Laende Urban Village Katobu Sub-District is a Sub-District which mostly utilizes Jompi spring to fulfill their daily needs. The purpose of this study was (1) to determine the environmental condition of the Jompi spring Laende Village Katobu District Muna Regency, (2) to describe the utilization of the Jompi spring Laende Village Katobu District Muna Regency. This research method uses qualitative descriptive research methods. Data collection techniques used were interviews and documentation study. The results of the research show that (1) the Jompi Spring Area which functions as a water catchment protected area and around the spring, physical and environmental conditions have experienced a decline with a lot of garbage, a decrease in water discharge based on data from the Duna Irrigation District of Muna, debit from the spring Jompi in 2010 amounted to Â± 25 liters / second. In this case it means that the debit has decreased ten times since the previous decade by Â± 50 liters / second, and experienced sedimentation in spring one, which was caused by flooding submissions from rivers in Labaha Village (2) Sources of Jompi spring most of it is used to meet the clean water needs of the people of Raha City that are accommodated by the PDAM and then distributed to the homes of residents not only that the source of water is also used for berendan and recreation. As for the remote areas in the city of water in the sub-education through pickup cars that are paid 25 thousand